Penyusutan dan Dimensi Serat Kayu Tumeh (Combretocarpus rotundatus Dans) pada Letak Radial: The Shrinkage and Fiber Dimension of Tumeh Wood (Combretocarpus rotundatus Dan) on Radial Positions - Supriyati, Wahyu; Alpian, Alpian; Yanciluk, Yanciluk (​Institute for Researches and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
The shrinkage of wood and the dimensions of wood fibers in the radial positions of stem are two important factors in the use of wood. An understanding of the dimension of wood fiber and the shrunkage of the wood in the radial direction can guide the optimum use of timber. The purpose of this study is to determine the shrinkage and changes in the dimensions of the timber (Combretocarpus rotundatus Dans) in the radial direction. The method used refers to the British and IAWA standards. The parameters measured are the radial and tangential shrinkage of wood as well as the dimensions of the fiber. The t test is used to test statistically. The results obtained showed that the position in the radial direction of the stem had a significant influence on the tangential shrinkage of fresh-oven dry and the fiber dimensions of Tumeh wood. The tangential shrinkage of the near pith is lower than that near the bark. The nearest pith part has a shorter fiber length; a thicker fiber wall is thinner than the near bark but still in the same quality class (Grade III) Keywords: tumeh, combretocarpus rotundatus, shrinkage, fiber dimension, radial positions.